(untitled) - Rowe, Harrison E. (New York, 1999)
This book presents analytic methods for calculating the transmission statistics of microwave and optical components with random imperfections. The emphasis here is on multi-mode waveguides, optical fibers, ans directional couplers - described by the coupled line equations with random parameters - as well as multi-layer optical coatings used as windows, mirrors, or filters.
Keywords: Electromagnetic waves,Fiber optics,Optical wave guides; Transmission